2016
DOI: 10.1111/bcpt.12577
|View full text |Cite
|
Sign up to set email alerts
|

Potential Future Pharmacological Treatment of Bladder Dysfunction

Abstract: In the last decades, a number of new antimuscarinic drugs have been introduced for treatment of the overactive bladder (OAB), defined symptomatically (OAB syndrome) or urodynamically (detrusor overactivity). Recently, three new drug principles have been approved for clinical use, the b 3 -adrenoceptor agonist, mirabegron, the phosphodiesterase-5 inhibitor, tadalafil and the blocker of afferent and efferent nerves, botulinum toxin. However, new alternatives are continuously being explored. OAB is a filling diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 155 publications
(247 reference statements)
2
54
0
Order By: Relevance
“…This effect might inhibit ATP release and delivery to sensory nerve terminals (Figure ), thereby inhibiting afferent nerve activity. Therefore, tadalafil might improve storage symptoms in BPH‐LUTS and be useful for the treatment of other diseases associated with TRPV2 and TRPV4, such as overactive bladder (Figure ) . The present study has several limitations worth noting.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This effect might inhibit ATP release and delivery to sensory nerve terminals (Figure ), thereby inhibiting afferent nerve activity. Therefore, tadalafil might improve storage symptoms in BPH‐LUTS and be useful for the treatment of other diseases associated with TRPV2 and TRPV4, such as overactive bladder (Figure ) . The present study has several limitations worth noting.…”
Section: Discussionsupporting
confidence: 87%
“…TRPV2 has also been shown to function in mouse urothelial cells . Studies of the lower urinary tract have indicated that several TRP channels expressed in the bladder act as sensors of stretch . However, the effects of PDE5‐I tadalafil on the mechanosensory functions of TRP channels in the bladder mucosa remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, these findings have demonstrated the potential importance of the cannabinoid receptors in the human bladder physiology and pathophysiology. As a result, these receptors have been viewed as a promising future direction in the pharmacotherapy of LUTS …”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have showed that DO is correlated with dysregulation of neurogenic and purinergic signaling that may lead to sensory‐ or motor‐activated incontinence . In addition, many researches also proposed that increased urinary ATP is the pathogenesis of OAB syndromes.…”
Section: Discussionmentioning
confidence: 99%